Antifungal effects of new heterocyclic compounds, 6H-pyrimido[2,1-a]isoindole derivatives - Nesmĕrák, K; Pelouchová, H; Vsetecka, V; Nĕmec, I; Gabriel, J (Folia microbiologica, 1998)
Minimal inhibitory concentrations for 10 new condensed isoindole derivatives were established by the agar diffusion method. Benzo[b]-6H-pyrimido[2,1-a]isoindole-4-one exhibited a broad antifungal effect; the observed MIC (mg/L) were 7 (K. lactis), 8 (C. pseudotropicalis), 17 (W. fluorescens), 22 (E. magnusii), 31 (P. membranaefaciens), 32 (S. alluvius) and 32 (S. cerevisiae). The compound also inhibited the growth of B. subtilis (MIC 9 mg/L). No effect on the growth of E. coli was found.
Keywords: heterocyklické sloučeniny tetra- a více cyklické; Antifungal Agents; Heterocyclic Compounds, 3-Ring; Microbial Sensitivity Tests; antifungální látky; heterocyklické sloučeniny tricyklické; Pyrimidines; Heterocyclic Compounds, 4 or More Rings; Indoles; pyrimidiny; mikrobiální testy citlivosti; indoly